Low Concentration of a Dioxin (2, 3, 7, 8 TCDD) Affects the Glycosidases and Acid Phosphatase Activity in Mice Hepatocytes - Jyoti Jigyasi; Rahul Kundu (SAGE Publishing, 2014)
Present communication reports the effects of environmentally available, low doses of tetra chloro di benzo-p-dioxin (2,3,7,8 TCDD) to lysosomal enzymes in mice liver. The study tests the hypothesis, in vivo exposure of low dose TCDD provokes dose and duration dependent toxic effects to key lysosomal enzymes and thereby causes cellular apoptotic changes. Three groups of female Swiss albino mice were subjected to two doses of TCDD (0.004 mg/kg bw/d, 0.04 mg/kg bw/d) for 2, 4 and 6 days of exposure durations. The results indicated significant exposure duration dependent effects of TCDD in mice liver cells. The results suggested that TCDD possibly induced an increase in intracellular ions or ROS which in turn altered different physiological activities by affecting different metabolic pathway of the liver cells. The altered functions of key lysosomal enzymes by TCDD may also evoke the process of cellular apoptosis.